Analysis of Non-Medical Logistics Procurement on the Availability of Goods In Hospital X Bandung - Salma Hanifah; Susanti, Ai Susi (CV. Science Tech Group, 2024)
This study aims to analyze the procurement of non-medical logistics related to the availability of goods at Hospital X Bandung. The research method used is qualitative, with data collection through interviews and direct observation. The findings show that the non-medical logistics procurement process involves several stages and parties, including the Head of Non-Medical Logistics Department, Logistics Manager, Director, Finance Department, and Business Actors. The accumulation of goods in the logistics department is caused by overstocking and inadequate storage space conditions. To address these issues, it is recommended to improve the inventory management system, provide training to staff, optimize storage space, improve coordination between parties, and conduct regular evaluations. This study emphasizes the importance of effective and efficient logistics management in supporting hospital operations and improving the quality of health services.